Strong signature of selection in seeder populations but not in resprouters of the fynbos heath Erica coccinea (Ericaceae) - Ojeda, Fernando; Niet, Timotheüs; Malan, Michelle C.; Midgley, Jeremy J.; Segarra‐Moragues, José G. (Botanical journal of the Linnean Society, 2016)
A higher frequency of natural selection is expected in populations of organisms with shorter generation times. In fire‐prone ecosystems, populations of seeder plants behave as functionally semelparous populations, with short generation times compared to populations of resprouter plants, which are truly iteroparous. Therefore, a stronger signature of natural selection should be detected in seeder populations, favoured by their shorter generation times and higher rates of population turnover. Here we test this idea in Erica coccinea from the Cape Floristic Region, which is dimorphic for post‐fire regeneration mode. We measured three floral traits supposedly subject to natural selection in seeder and resprouter populations. We then compared phenotypic trait variation with neutral genetic variation in each group of populations using PST–FST comparisons to detect signatures of natural selection in seeders and resprouters. We found a strong signature of selection in seeder populations, but not in resprouters. Furthermore, anthers of seeders were more exserted (and larger) than those of resprouters. These differences were maintained at sites where seeders and resprouters co‐occurred, suggesting that phenotypic plasticity or adaptation to different growth environments are unlikely explanations for trait variation. These results provide empirical support for the hypothesis that the genetic signature of natural selection is certainly more intense in seeder than in resprouter populations, favoured by their comparatively faster generation turnovers. Increased frequency of natural selection would increase differentiation among populations, thus promoting speciation in pyrophytic seeder lineages of the Cape flora.